2012
DOI: 10.1002/14651858.cd006655.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy versus laparotomy for the management of early stage endometrial cancer

Abstract: This review has found evidence to support the role of laparoscopy for the management of early endometrial cancer.For presumed early stage primary endometrioid adenocarcinoma of the endometrium, laparoscopy is associated with similar overall and disease-free survival. Laparoscopy is associated with reduced operative morbidity and hospital stay. There is no significant difference in severe post-operative morbidity between the two modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
124
1
18

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(151 citation statements)
references
References 41 publications
8
124
1
18
Order By: Relevance
“…Endometrial cancer is the most common gynecologic cancer treated with laparoscopic surgery. It is feasible and has less operative morbidity, less blood loss, shorter hospitalizations, and better short-term quality of life than the laparotomy approach (Kornblith et al, 2009;Galaal et al, 2012;Wang et al, 2013). Similar results were reported for laparoscopic radical hysterectomy in cervical cancer (Magrina et al, 2008).…”
Section: Introductionsupporting
confidence: 57%
“…Endometrial cancer is the most common gynecologic cancer treated with laparoscopic surgery. It is feasible and has less operative morbidity, less blood loss, shorter hospitalizations, and better short-term quality of life than the laparotomy approach (Kornblith et al, 2009;Galaal et al, 2012;Wang et al, 2013). Similar results were reported for laparoscopic radical hysterectomy in cervical cancer (Magrina et al, 2008).…”
Section: Introductionsupporting
confidence: 57%
“…Even though, less invasive approaches such as laparoscopic or vaginal procedures are suggested primarily, the standard procedure for most cases is abdominal hysterectomy [7,8]. The major causes for counselling vaginal or laparoscopic hysterectomy over the abdominal method is earlier beginning of routine actions, shorter hospital stay, fewer bleeding, and fewer infections.…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive surgery in these women has already resulted in shorter length of stay and less complications. 3 Recent studies have shown the benefit of introducing a robotic service in primary surgery for endometrial cancer, showing less conversions to laparotomy and a reduction in the number of laparotomies performed. 4,5 Obesity is one of the comorbidities related to an increase in operating time, complications, and length of stay.…”
Section: Introductionmentioning
confidence: 99%
“…There is clear evidence from both individual randomized controlled studies and a respected meta-analysis 3 that some form of laparoscopic approach is associated with less complications and a similar survival. Therefore, laparotomy is no longer the preferred route for endometrial cancer in women who are not contraindicated to have some form of laparoscopic approach.…”
mentioning
confidence: 99%